The Research on CC2530 Nodes Communicating with Each Other Based on Wireless - Zhenghua Xin; Hong Li; Liangyi Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This work has completed the communication between the CC2530 coordinator and the child CC2530 nodes based on the Zigbee protocol. In this system, the object is detected by the CC2530 ultrasonic nodes. The distance is calculated and the message is formed. The message is sent to the coordinator by IIC bus which includes the control instruction. The coordinator receives the control information and will issue a command to control alcohol sensor to control the motor interface. The system can control the motor forward, backward and keep the DC motor still. The system can be widely used in agriculture and other fields. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1919